PENGARUH LAMANYA DIABETES MELITUS TERHADAP TERJADINYA DISFUNGSI EREKSI - Dodie, Natasya Juliani; Tendean, Lydia; Wantouw, Benny (e-Biomedik, 2013)
Abstract: Diabetes mellitus is a condition with excess glucose in the blood which can lead to complications such as chronic diseases, among others cardiovascular disease and sexual dysfunction such as erectile dysfunction. This study aimed to determine the effect of duration of diabetes mellitus on the occurrence of erectile dysfunction. This was an analytic survey with cross sectional study design. Samples were 30 respondents, taken by simple random sampling. Data were collected by using a questionnaire IIEF-5 (International Index of Erectile Function) and the data were univariate analyzed. The results showed that there were 20 people suffered from erectile dysfunction out of 30 respondents. The univariate analysis showed that erectile dysfunction respondents that had diabetes mellitus for 1-4 years were 11 people (36.7%); and that had diabetes mellitus for 5-8 years were 19 people (63.3%). The statistical parametric test T-Test found a significant relationship between the duration of diabetes mellitus and erectile dysfunction with P = 0.025 (a significance level of 0.05). Conclusion: Long duration of diabetes mellitus can lead to erectile dysfunction. Keywords: diabetes mellitus, erectile dysfunction. Abstrak: Diabetes melitus adalah suatu keadaan dimana terdapat kadar gula berlebihan dalam darah yang dapat mengakibatkan komplikasi berupa penyakit-penyakit kronis seperti penyakit kardiovaskuler dan disfungsi seksual, salah satunya disfungsi ereksi. Penelitian ini bertujuan untuk mengetahui pengaruh lamanya diabetes melitus terhadap terjadinya disfungsi ereksi. Penelitian ini bersifat survei analitik dengan desain penelitian cross sectional. Sampel berjumlah 30 orang yang diambil secara simple random sampling. Data dikumpulkan dengan menggunakan kuesioner IIEF-5 (International Index of Erectile Function) dan data dianalisis secara univariat. Dari penelitian ini didapatkan 20 orang dengan kejadian disfungsi ereksi pada penderita diabetes melitus dari 30 orang responden. Analisa univariat menunjukkan bahwa responden yang mengalami disfungsi ereksi pada pria dengan diabetes melitus selama 1-4 tahun berjumlah 11 orang (36,7%), dan dengan diabetes melitus selama 5-8 tahun berjumlah 19 orang (63,3%). Uji parametrik T-Test memperlihatkan terdapat hubungan bermakna antara diabetes melitus yang lama dengan terjadinya disfungsi ereksi dengan nilai P = 0,025 dengan tingkat signifikansi 0,05. Simpulan: Diabetes melitus yang lama bisa mengakibatkan terjadinya disfungsi ereksi. Kata kunci: diabetes melitus, disfungsi ereksi.